ANALYSIS OF THE IMPACT OF FLOATING NET CAGES ON WATER QUALITY OF LAKE BULILIN, SOUTHEAST MINAHASA REGENCY NORTHSULAWESI PROVINCE (Novateur Publications, 2023)
Pollution that occurs in the waters of Lake Bulilin is thought to originate from the flow (input) of the waste load of community activities that take place in indogenously (lake water bodies) and exogenously (outside the lake). Waste originating from activities that take place in water bodies originates from KJA activities. The organic waste load sourced from KJA in the form of leftover feed and fish feces can reduce the quality of lake waters. In addition to this, the decline in water quality is also caused by waste originating from outside the lake in the form of domestic waste, waste from agricultural and livestock activities around the lake waters. Based on this, the following research problems can be formulated: (1) What is the quality of the waters and the level of water pollution in Lake Bulilin, Southeast Minahasa Regency, North Sulawesi Province. (2) What is the public's perception of the Lake Bulilin KJA, Southeast Minahasa Regency, North Sulawesi Province. The aims of the study were: (1) to analyze the water quality and contamination level of Lake Bulilin waters. (2) Analyzing the public's perception of the Lake Bulilin KJA. Based on the results of the study, it can be concluded that: (1) The water quality display for Lake Bulilin has exceeded class 1 water quality standards, based on PP. No. 82 of 2001 which is designated as a source of raw water for drinking water is BOD5, COD, fecal coliform, and total coliform. Based on the Aquatic Environmental Quality Index (IMPL), the quality of the waters of Bulilin Lake is included in the moderate or slightly polluted quality category. (2) The community's perception ofthe impact of KJA on the quality of lake waters around their residence is relatively negative, meaning that the community believes that the aquatic environment of the lake has been polluted by KJA, which is increasing in abundance in Lake Bulilin